2021
DOI: 10.1038/s41598-021-90043-7
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of antiretroviral therapy initiation in the era before universal treatment

Abstract: We assessed the prevalence and factors related to the time to antiretroviral (ART) initiation among persons who entered HIV care and subsequently started ART in Croatia from 2005 to 2014. Included were patients ≥ 18 years, the follow-up ended on Dec/31/2017. 628 patients were included into the study 91.9% were men; median age was 36.1 (Q1–Q3: 29.6–43.8) years. Rapid (within 7 days of diagnosis) ART initiation was observed in 21.8% patients, 49.8% initiated ART within 30 days, 21.7% and 28.5% had intermediate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
(26 reference statements)
2
11
0
Order By: Relevance
“…This result is in line with study results from Kampala, Uganda that reported the median time to ART initiation was 6 days, 8 and review of evidence regarding rapid ART initiation, which revealed that newly diagnosed HIV-positive individuals on average started ART within 7 days of a confirmed positive HIV diagnosis. 37 However, this is shorter than in study results conducted in Myanmar, 32 Croatia, 38 and Melbourne, Australia 39 which reported the median time to ART initiation as of 29, 30, and 77 days respectively. The variation may be due to the different criteria used to initiate ART for newly diagnosed HIV-positive individuals.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…This result is in line with study results from Kampala, Uganda that reported the median time to ART initiation was 6 days, 8 and review of evidence regarding rapid ART initiation, which revealed that newly diagnosed HIV-positive individuals on average started ART within 7 days of a confirmed positive HIV diagnosis. 37 However, this is shorter than in study results conducted in Myanmar, 32 Croatia, 38 and Melbourne, Australia 39 which reported the median time to ART initiation as of 29, 30, and 77 days respectively. The variation may be due to the different criteria used to initiate ART for newly diagnosed HIV-positive individuals.…”
mentioning
confidence: 71%
“…The median age of newly diagnosed HIV positive people was 35 [IQR: [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] years. The majority of the study participants (164; 31.66%) were found in age category of ≥40 years old.…”
Section: Socio-demographic Characteristics Of Study Participantsmentioning
confidence: 99%
“…The median (IQR) survival time-to-ART-initiation in the present study was 6 (IQR: 0-5414) days. This finding is similar to 5 (IQR 1-13) days median time from West African countries – Burkina Faso, Cote d’ Ivoire, Mali, and Togo, [94], and similar to 4 (IQR 1-9) days from Ethiopia study [95] but was much lower than 29 (IQR: 0-514) days from UK study [73], lower than 21 (IQR: 17-39) days from Portugal [96] and from Republic of South Africa (RSA) [97] and, than 31 (QI-Q3: 8-537.5) days in Croatia [98]. Furthermore, in another RSA study, median time to ART-initiation was 12 (IQR: 1-59) days [99].…”
Section: Discussionmentioning
confidence: 95%
“…As a marker of response to ART, viral loads were mostly used to monitor therapy effectiveness following initiation [7]. The present UTT strategy of initiating ART early with definitive lag-time references [98], is the update of initial recommendations of commencing ARVs during “early” HIV infection; where “early” was defined as period up to 6 months after HIV diagnosis [130–133]. In line with current global recommendations, Malawi adopted the UTT strategy in 2016 and embedded it in her successive “Integrated clinical guidelines for HIV management” [134, 135].…”
Section: Discussionmentioning
confidence: 99%
“…Croatia has a centralized system of HIV care, and all persons living with HIV (PLWH) are treated at the University Hospital for Infectious Diseases (UHID) in Zagreb [ 5 , 6 , 7 ]. The PrEP service was introduced in Croatia as a pilot project in September 2018, and this service is still available only at the HIV Outpatient Department at the UHID in Zagreb.…”
Section: Methodsmentioning
confidence: 99%